Sistem Diversi Pada Tindak Pidana Narkotika oleh Anak yang Berkonflik dengan Hukum - Mutiara Adival, Julisya; Firmansyah, Hery (Universitas Ekasakti, 2023)
The crime of narcotics abuse in camping continues to grow, with trafficking involving children. The status of children who are vulnerable to unlawful acts means that the justice system must also consider the child's condition. Therefore, in the Indonesian justice system, the term 'juvenile criminal justice' is known, which is specifically applied to criminal acts committed by children. This also means that various criminal acts, such as narcotics crimes committed by children, must also be tried appropriately. As happened to the child defendant in decision no. 9/Pid.Sus-Anak/2022/Pn JKT.SEL. In this case study, children were involved as intermediaries in buying and selling narcotics. Based on this background, the aim of this research was to understand the criminal justice process in narcotics crimes against children, as well as the laws that can be used as a basis for justice applied to children. The research was carried out as a normative type of research, with a statutory and case study approach. The results of this research show that the administration of juvenile justice in Indonesia for narcotics crimes that make children suspects is carried out using a restorative justice approach with a diversion system. Even so, the judge still takes into account the demands of the prosecutor, and also the legal conditions that occurred. So that the judicial process can be relevant to the diversion that has been implemented. Meanwhile, the laws used as the basis for determining punishment consist of the Law on Narcotics, the Law on the Juvenile Criminal Justice System and the 1945 Constitution of the Republic of Indonesia concerning judicial power.